2014
DOI: 10.5424/sjar/2014124-6173
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between six eastern Pyrenean sheep breeds assessed using microsatellites

Abstract: The knowledge of the genetic composition and relationships among livestock breeds is a necessary step for the implementation of management and conservation plans. This study aims to characterise the genetic diversity and relationships among six sheep breeds of meat aptitude that are spread through the eastern Pyrenees: Tarasconnaise, Castillonnaise and Rouge du Roussillon from France, and Aranesa, Xisqueta and Ripollesa from Spain. All but Tarasconnaise are catalogued as endangered. These breeds do not share t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
2
5
0
1
Order By: Relevance
“…Furthermore, the effective number of alleles was calculated among the breeds, where Ne value ranged from 3.902±0.477 to 4.975±0.461.The obtained indicators were similar to the result of S.B.S. Gaouaret al (2016) and greater than the values reported by X. C. Zeng et al (2010) [27][28]. In order to compare the genetic variability of the three sheep breeds, the observed and expected heterozygosity was estimated for each pair of populations (Table 2).…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the effective number of alleles was calculated among the breeds, where Ne value ranged from 3.902±0.477 to 4.975±0.461.The obtained indicators were similar to the result of S.B.S. Gaouaret al (2016) and greater than the values reported by X. C. Zeng et al (2010) [27][28]. In order to compare the genetic variability of the three sheep breeds, the observed and expected heterozygosity was estimated for each pair of populations (Table 2).…”
Section: Discussionsupporting
confidence: 76%
“…Ferrando et al (2014) also found close F ST value in six breeds located in the eastern Pyrenees ranging from 0.011 to 0.053. When Saudi sheep populations were compared with other populations from different countries, the F ST values were lower than those found in this study (Sassi-Zaidy et al, 2014;Álvarez et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
“…Purity and concentration of each sample was quantified using NanoDrop 2000 spectrophotometer (Thermo Scientific, Wilmington, Delaware, USA). These markers were selected by taking into account the level of polymorphism previously detected in other studies and the location on different chromosomes (Peter et al, 2007;Ferrando et al, 2014;Yilmaz et al, 2015). Polymerase chain reaction (PCR) amplifications were carried out in a 25 µl reaction volume containing100 ng of template DNA and 2 µl of each 10 µM primer.…”
Section: Methodsmentioning
confidence: 99%
“…The mean Fst values among the three sheep populations ranged between 0.031 (between Naeimi and Herri populations), 0.033 (between Najdi and Naeimi populations) and 0.017 (between Najdi and Herri populations) indicating little genetic differentiation among Saudi sheep populations. Ferrando et al (2014) also obtained close Fst value in six breeds located in the eastern Pyrenees ranging from 0.011 to 0.053. When Saudi Arabian sheep populations were compared with other populations from different countries, the lower Fst values were observed in this study (Sassi-Zaidy et al, 2014).…”
Section: Resultsmentioning
confidence: 68%